Differences in risk of serious infections between patients with secondary versus primary nephropathy following rituximab treatment: a retrospective cohort study - Xu, Jing; Ding, Ying; Qu, Zhen; Yu, Feng (Frontiers in Immunology, 2024)
The incidence of severe infections (SIs) in patients with autoimmune nephropathy after rituximab (RTX) treatment varies significantly. Our study aims to identify high-risk populations, specifically by comparing the differences in the risk of SIs between patients with primary nephropathy and those with nephropathy in the context of systemic autoimmune diseases (referred to as secondary nephropathy). Methods: This retrospective cohort study investigated the occurrence of SIs in adult patients with immune-related kidney disease who received RTX treatment at our institution from 2017 to 2022. Multivariable COX regression models were used to analyze the association between the type of nephropathy (primary or secondary) and SIs. Propensity score analyses, subgroup analyses, and E-value calculations were performed to ensure the reliability of the results. Results: Out of 123 patients, 32 (26%) developed 39 cases of SIs during a mean follow-up period of 19.7 ± 14.6 months post-RTX treatment, resulting in an incidence rate of 18.9/100 patient-years. The multivariable COX regression analysis indicated that patients with secondary nephropathy had a significantly higher risk of SIs compared to those with primary nephropathy (HR = 5.86, 95% CI: 1.05-32.63, P = 0.044), even after accounting for confounding variables including gender, age, BMI, history of prior SIs, baseline eGFR, lymphocyte counts, IgG levels, and the utilization of other immunosuppressive therapies. Various sensitivity analyses consistently supported these findings, with an E-value of 5.99. Furthermore, advanced age (HR: 1.03; 95% CI: 1.01-1.06; P = 0.023), low baseline IgG levels (HR: 0.75; 95% CI: 0.64-0.89; P < 0.001), and recent history of SIs (HR: 5.68; 95% CI: 2.2-14.66; P < 0.001) were identified as independent risk factors. Conclusion: The incidence of SIs following RTX administration in patients with autoimmune nephropathy is significant. It is crucial to note that there are distinct differences between the subgroups of primary and secondary nephropathy. Patients with secondary nephropathy, particularly those who are elderly, have low baseline IgG levels, and have a recent history of SI, are more susceptible to SIs.